Correlation between preoperative ultrasonographic airway assessment and laryngoscopic view in adult patients: A prospective study - Aruna Parameswari; Mithila Govind; Mahesh Vakamudi (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: Difficult tracheal intubation is associated with serious morbidity and mortality and cannot be always predicted based on preoperative airway assessment using conventional clinical predictors. Ultrasonographic airway assessment could be a useful adjunct, but at present, there are no well-defined sonographic criteria that can predict the possibility of encountering a difficult airway. The present study was conducted with the aim of finding some correlation between preoperative sonographic airway assessment parameters and the Cormack-Lehane (CL) grade at laryngoscopic view in adult patients. Material and Methods: This was a prospective, double-blinded study on 130 patients undergoing elective surgery under general anesthesia. Preoperative clinical and ultrasonographic assessment of the airway was done to predict difficult intubation and was correlated with the CL grade noted at laryngoscopy. The sensitivity, specificity, positive predictive value, and negative predictive values of the parameters were assessed. Results: The incidence of difficult intubation was 9.2%. Among the clinical predictors, the modified Mallampati classification had the maximum sensitivity and specificity, and among the sonographic parameters, the skin to epiglottis distance had the maximum sensitivity and specificity to predict difficult laryngoscopy. A combination of these two tests improved the sensitivity in predicting a difficult laryngoscopy. Conclusions: The skin to epiglottis distance, as measured at the level of the thyrohyoid membrane, is a good predictor of difficult laryngoscopy. When combined with the modified Mallampati classification, the sensitivity of the combined parameter was found to be greater than any single parameter taken alone.